2013
DOI: 10.12968/jowc.2013.22.12.699
|View full text |Cite
|
Sign up to set email alerts
|

Superior gluteal artery perforator flap: A reliable method for sacral pressure ulcer reconstruction

Abstract: There were no external sources of funding for this study. The authors have no conflicts of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…In the current study, we did not skeletonize the perforator vessel for any of the flaps. In agreement with that, Khurram et al, [11] reported that full perforator skeletonization increased the risk of perforator twist, kink or injury, resulting in complications like vasospasm, blood flow blockage and eventually total flap loss. Koshima et al, approved the same concept of flap safety, while Verpaele et al, opposed it and recommended the need for full vessel skeletonization [17].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the current study, we did not skeletonize the perforator vessel for any of the flaps. In agreement with that, Khurram et al, [11] reported that full perforator skeletonization increased the risk of perforator twist, kink or injury, resulting in complications like vasospasm, blood flow blockage and eventually total flap loss. Koshima et al, approved the same concept of flap safety, while Verpaele et al, opposed it and recommended the need for full vessel skeletonization [17].…”
Section: Discussionsupporting
confidence: 87%
“…In our study, most of the studied patients (80%) were paraplegic, while some (20%) were ambulatory. Khurram et al, [11] agreed with us and reported 73.3% of their patients were paraplegic.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, perforator flaps have become many centers' preferred reconstructive method for sacral pressure sores. Although the reliability of superior gluteal artery, inferior gluteal artery, and lateral sacral artery perforator flaps in sacral reconstruction were shown in various studies, perforator flaps have some drawbacks, especially in large sacral pressure ulcers (Coskunfirat & Özgentas, 2004; Durgun & Bas, 2019; Khurram et al, 2013; Seyhan et al, 2008; Ulusoy et al, 2001). Large defects can be closed by planning contralateral flaps or truly dissected perforator flaps with a high rotation arc or multilobed flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Once deep tissue infection is noted, in-hospital care, along with surgical interventions, 2 of 8 is beneficial for patients. Several different kinds of flaps have been introduced over the years to reconstruct sacral defects, such as local flaps, V-Y advancement fasciocutaneous flaps, gluteus maximum muscle-based flaps, inferior gluteal artery perforator flaps, and superior gluteal artery perforator (SGAP) flaps [1]. Reliable perforators are the most important factors for a successful perforator-based flaps reconstruction [2].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an accurate preoperative mapping of the perforators is essential for the safe planning of propeller flaps. To date, various methods have been reported: (1) handheld acoustic Doppler sonography (ADS), (2) color duplex sonography, (3) perforator computed tomographic angiography (P-CTA), (4) magnetic resonance angiography, and (5) indocyanine green fluorescence nearinfrared angiography (ICGFA) [3,4]. Out of these ways of mapping perforators, the golden standards are perforator computed tomographic angiography (P-CTA) and the magnetic resonance angiograph.…”
Section: Introductionmentioning
confidence: 99%